Long-Term Effect of GPi-DBS in a Patient With Generalized Dystonia Due to GLUT1 Deficiency Syndrome - Hanci, Idil; Kamm, Christoph; Scholten, Marlieke; Roncoroni, Lorenzo P.; Weber, Yvonne; Krüger, Rejko; Plewnia, Christian; Gharabaghi, Alireza; Weiss, Daniel (Frontiers in Neurology, 2018)
Treatment outcomes from pallidal deep brain stimulation are highly heterogeneous reflecting the phenotypic and etiologic spectrum of dystonia. Treatment stratification to neurostimulation therapy primarily relies on the phenotypic motor presentation; however, etiology including genetic factors are increasingly recognized as modifiers of treatment outcomes. Here, we describe a 53 year-old female patient with a progressive generalized dystonia since age 25. The patient underwent deep brain stimulation of the globus pallidus internus (GPi-DBS) at age 44. Since the clinical phenotype included mobile choreo-dystonic features, we expected favorable therapeutic outcome from GPi-DBS. Although mobile dystonia components were slightly improved in the long-term outcome from GPi-DBS the overall therapeutic response nine years from implantation was limited when comparing ‘stimulation off’ and ‘stimulation on’ despite of proper electrode localization and sufficient stimulation programming. In order to further understand the reason for this unexpectedly limited motor symptom response, we aimed to clarify the etiology of generalized dystonia in this patient. Genetic testing identified a novel heterozygous pathogenic SLC2A1 mutation as cause of glucose transporter type 1 deficiency syndrome (GLUT1-DS). This case report presents the first outcome of GPi-DBS in a patient with GLUT1-DS, and suggests that genotype relations may increasingly complement phenotype-based therapy stratification of GPi-DBS in dystonia.